A tecnologia no capitalismo dependente: a superexploração da força de trabalho em Karl Marx e Ruy Mauro Marini - Teles, Gabriela Caramuru (2017)
The present works looks over the tecnological development spefically from the countries in Latin America. Therefore making the use of the work “Capital”, by Karl Marx and selected works by Ruy Mauro Marini, a theorical reference of the Marxist Dependency Theory. The goal of this work consists in analyzing the role of technology in the dependant economies of Latin America from the categories of Marx and Marini, in the context of the super-exploitation of work and trasnference of capital. The justification of this research is the need to overcome the eurocentric views and reproductions on technological development and to undestand technology in Latin America under the inquest of Historic Materialism. With unequal trades, tecnology import and public debt we verify a brutal transference of capital from Latin America. As a compensation policy of loss by transference, the strategy of super-exploitation of workforce is largely used - intensification of work, extended work hours and payments under the production value. With markets reduced by low incomes, we witness a divorce between production and the making of goods, in a way that the good produced by dependent countries are mostly consumed by central countries. Thereby aggravating the international division of work, where Latin American countries produce cheap feedstock for exportation and central countries have their productive axis in industrialization. This particular character of exploitation of work in Latin America reveals underdevelopment as a permanent relashionship between dependent and central countries, exhibiting also internal dependency in dependent countries. Thus, we can verify a consolidation of more complex production stages in the Center and less complex ones in dependent countries. So, the Latin American technological development finds itself limited by the boudaries of central countries, with: industrialization lined by production of capital goods by the Center; importation of obsolete technological packets to refund the machinery discarded in the Center by the competition; the use of super-explited work force in detrimento of machinery use; technological development, but restricted only to a manufacturing island and not generalized; never to cheapen the goods cosumed by workers; super-exploitation as a movement to compete with more productive manufacturing islands; or yet the dependency on international capital for investments. The dissertation defends that, for Ruy Mauro Marini, the technological development in Latin America didn’t mean a raise in productivity with the cheapen of goods, and hence the improvement of life quality for workers. But, in na opposite direction, it is an element of the super-exploitation of work and leads to the intensification of work as a movement of competition with isolated and most productive branches in the internal scope, related to international production.